2021
DOI: 10.1177/23337214211052201
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Computer-Mediated Communication (CMC) Engagement Following COVID-19 and Its Impact on Access to Community, Information, and Resource Exchange: A Longitudinal, Qualitative Study

Abstract: Following COVID-19, the CDC asked individuals to social distance and state and local authorities nationwide began issuing curfews and recommendations to “shelter-in-place.” Known to be more susceptible to the negative effects of COVID-19 and often coping with higher levels of social isolation, many worried that older adults’ mental health would suffer. While computer-mediated communication (CMC) is on the rise among older adults, whether and how older adults leverage the social benefits of CMC remains underexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The extant qualitative literature provides a more nuanced view of the lived experience of older adults during that time, and offers a rich source of information about the ways that older adults responded to the pandemic. For example, Mikal et al (2021) followed 22 older adults for 6 weeks during the pandemic, using longitudinal qualitative surveys as a means to study digital engagement and mental health outcomes. They found that older adults effectively used social media for entertainment and education, but were less comfortable accessing online resources, and struggled with larger social media communities, preferring one-to-one communication.…”
Section: Background Literature 21 Older Adults and The Digital Dividementioning
confidence: 99%
“…The extant qualitative literature provides a more nuanced view of the lived experience of older adults during that time, and offers a rich source of information about the ways that older adults responded to the pandemic. For example, Mikal et al (2021) followed 22 older adults for 6 weeks during the pandemic, using longitudinal qualitative surveys as a means to study digital engagement and mental health outcomes. They found that older adults effectively used social media for entertainment and education, but were less comfortable accessing online resources, and struggled with larger social media communities, preferring one-to-one communication.…”
Section: Background Literature 21 Older Adults and The Digital Dividementioning
confidence: 99%